Psychological Meaningfulness and Work Engagement Effect on Doctor’s Job Satisfaction - Purba, Sylvia Diana; Chaterine, Chaterine; Hardjono, Saebani; Clarissa, Bella (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
This research aims to investigate the job satisfaction of the doctors with psychological meaningfulness and work engagement as antecedent variables, in Java, Indonesia. The sampling technique used in this research was convenience sampling method and snowball sampling method. To analyze the data, this research used the SEM program, assisted with AMOS 23. The results of this study indicate that psychological meaningfulness effect on work engagement. However, no effect on job satisfaction. While the work engagement has an effect on job satisfaction. The work engagement is significant as intervening variable in the influence of psychological meaningfulness toward job satisfaction. These results support the work situation of doctors in Indonesia who have high workloads but can still feel job satisfaction. High work engagement will make the doctors feel enthusiasm and dedication even though the workload is high with abnormal work hours. These results support the work situation of doctors in Indonesia who have high workloads but can still feel job satisfaction.